Subgroup analysis based on cytogenetic risk in patients with relapsed or refractory multiple myeloma in the CANDOR study - Landgren, Ola; Weisel, Katja; Rosinol, Laura; Touzeau, Cyrille; Turgut, Mehmet; Hajek, Roman; Mollee, Peter; Kim, Jin Seok; Shu, Natalie; Hu, Xuguang; Li, Chuang; Usmani, Saad Z (British journal of haematology, 2022)
CANDOR compared the safety/efficacy of carfilzomib with dexamethasone and daratumumab (KdD) to carfilzomib with dexamethasone (Kd) in adults with relapsed/refractory multiple myeloma (RRMM). This CANDOR subgroup analysis evaluated outcomes based on cytogenetic risk. Overall response rates (KdD vs. Kd) were 81% versus 56% in high-risk and 87% versus 79% in standard-risk groups. Median progression-free survival was 11.2 versus 7.4 months in high-risk (hazard ratio, 0.56 [95% CI, 0.34, 0.93]) and not reached versus 16.6 months in standard-risk groups (0.56 [95% CI, 0.39, 0.80]). These data support the efficacy of KdD in RRMM treatment, including in patients with high-risk cytogenetics.
Keywords: dospělí; carfilzomib; Adult; cytogenetics; výsledek terapie; cytogenetické vyšetření; relapsed or refractory multiple myeloma; lidé; mnohočetný myelom; Cytogenetic Analysis; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; prognóza; protokoly protinádorové kombinované chemoterapie; dexamethason; Dexamethasone; Prognosis; Multiple Myeloma; proteasome inhibitor; Humans